2014
DOI: 10.1177/0960327114538988
|View full text |Cite
|
Sign up to set email alerts
|

Increased oxidative stress and activated heat shock proteins in human cell lines by silver nanoparticles

Abstract: Due to widely commercial applications of silver nanoparticles (Ag NPs), toxicity assessment of this NP is of great importance. This study aimed to investigate the oxidative stress and heat shock response of Ag NPs at different doses to A549 and HepG2 cells. After treatment with different concentrations of Ag NPs for 24 h, oxidative damage indicated by malondialdehyde (MDA), 8-epi-PGF2α, and 8-hydroxy-2′-deoxyguanosine (8-oxo-dG) concentrations and protein levels of heat shock protein A1A (HSPA1A) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 39 publications
3
25
0
Order By: Relevance
“…The AgNPs with < 100 nm particle size were characterized by TEM and DLS analysis as described previously (Xin et al , ). The TEM analysis showed that the primary particles of AgNPs were spherical and approximately 20–50 nm in diameter.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…The AgNPs with < 100 nm particle size were characterized by TEM and DLS analysis as described previously (Xin et al , ). The TEM analysis showed that the primary particles of AgNPs were spherical and approximately 20–50 nm in diameter.…”
Section: Resultsmentioning
confidence: 69%
“…No.576832) AgNPs, with < 100 nm particle size, were purchased from Sigma‐Aldrich. The AgNPs were characterized by transmission electron microscope (TEM; HITACHI H‐600, Tokyo, Japan) and Dynamic light scattering (DLS) as described previously (Xin et al , ). Zeta potential analysis was also conducted in this study.…”
Section: Methodsmentioning
confidence: 99%
“…However, the use of Ag NP is debated because of their toxicity in vivo and in many cell types in vitro [6,7,8,9,10,11], even though in several cases the underlying mechanisms have not been elucidated. Initially, we focused on human osteoblast-like cells and found a dose dependent toxic effect of Ag NP, with an IC 50 around 25 µg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…Ag NP cause abnormalities in zebrafish development in a dose-dependent manner [6] and are toxic for a variety of normal and neoplastic cells [7,8,9,10,11] mainly by generating oxidative and nitrosative stresses [9,10]. Since nanoparticulate silver coatings for orthopedic implants represent a promising approach to prevent infections, the effects of Ag NP have been studied on bone cells.…”
Section: Introductionmentioning
confidence: 99%
“…17 In addition, AT-III activity is a plasma coagulation inhibitor, which is significantly lower under exposure to endosulfan. 23 vWF is one of the most important biomarkers for endothelial cell injury. The above results indicated that endosulfan may cause the hypercoagulability of blood by promoting platelet aggregation and the transformation of fibrinogen into fibrin on the one hand, and by depressing AT-III activity on the other hand.…”
Section: Discussionmentioning
confidence: 99%